Exercise capacity affects quality of life in patients with pulmonary hypertension - Halank, Michael; Grünig, Ekkehard (Lung, 2013)
The objective of this prospective study was to evaluate the impact of exercise capacity, mental disorders, and hemodynamics on quality-of-life (QoL) parameters in patients with pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH).
Gesehen am 25.02.2021